Pengaruh Penambahan Karagenan Terhadap Total Asam Minuman Jelly Sari Buah Kuini (Mangifera Odorata Griff) - Pebrianto Saputra; Lisa Yusmita; Isril Berd (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
This research was conducted to increase the selling value of kuini, because kuini is a fruit that is quite popular with the public because of the combination of sweet and sour taste in kuini, but kuini has a low shelf life because it is easily rotten caused by pests. The existence of kuini is abundant at the time of large harvest, but it is not accompanied by absorption in the market, causing losses at the level of kuini farmers. Therefore, it is necessary to process the kuini into a form of diversification of food products so that it can compete in the market and be able to increase the economic value of the kuini. This study aims to determine the effect of adding carrageenan to the total acid of the kuini juice jelly drink. The design used in this study was a completely randomized design (CRD) with 5 different treatments. Observational data were analyzed by means of variance (ANOVA) if significantly different, the DNMRT (Duncan New Multiple Range Test) test was carried out at a 5% significance level. The treatment of this research is the difference in the addition of carrageenan. The five treatments were A (Additional Carrageenan 0.2%), B (Add Carrageenan 0.4%), C (Add Carrageenan 0.6%) D (Add Carrageenan 0.8%), E (Add Carrageenan 1.0 %). The results showed that the addition of carrageenan had no significant effect on the total acidity of the kuini juice jelly drink.